2005
DOI: 10.1123/jab.21.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Jumping Reorganization with Aging: A Kinematic Comparison between Young and Elderly Men

Abstract: To our knowledge jumping kinematics have never been studied in elderly persons. This study was aimed at examining the influence of aging on vertical jump performance and on interjoint coordination. Two groups of adults, 11 young men ages 18–25 years and 11 older men ages 79–100 years, were filmed while performing a maximal squat jump. Compared to young adults, jump height was significantly decreased by 28 cm in the elderly. Older adults spontaneously jumped from a more extended position of the hip. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…The CMJ movement could be readily performed by all subjects in our group of community-dwelling healthy elderly women. Furthermore, numerous studies have performed maximal vertical jumping (CMJ and/or squat jump) in old subjects (up to 100 years) without reporting methodological problems (Bosco & Komi, 1980;Paasuke et al, 2000;Caserotti et al, 2001;Rittweger et al, 2004;Haguenauer et al, 2005). It cannot be excluded, however, that individuals with serious musculoskeletal problems (i.e., back pain or arthritis) would have difficulties in performing the CMJ without pain.…”
Section: Limitations Of Cmj Testing In Elderly Individualsmentioning
confidence: 99%
“…The CMJ movement could be readily performed by all subjects in our group of community-dwelling healthy elderly women. Furthermore, numerous studies have performed maximal vertical jumping (CMJ and/or squat jump) in old subjects (up to 100 years) without reporting methodological problems (Bosco & Komi, 1980;Paasuke et al, 2000;Caserotti et al, 2001;Rittweger et al, 2004;Haguenauer et al, 2005). It cannot be excluded, however, that individuals with serious musculoskeletal problems (i.e., back pain or arthritis) would have difficulties in performing the CMJ without pain.…”
Section: Limitations Of Cmj Testing In Elderly Individualsmentioning
confidence: 99%
“…Fingertip trajectory concavity depends also on the spatial position of the target to reach and increase from ipsilateral to contralateral sides [20]. In human jumping and animal leaping, we showed that, whereas the magnitude of the velocity vector increased all along the CoM trajectory during push-off, its orientation was reached at 20% of total push-off time in Microcebus murinus [21] and at 40% in humans [22] and then remained constant. In other words, after an orientation phase of the body CoM, these species tend to maintain their trajectory linear.…”
Section: Introductionmentioning
confidence: 75%
“…~ 300°/s) of typical isokinetic devices. For instance, humeral internal rotation velocity during throwing (overhand pitching) may reach 130–134 rad/s and knee and ankle angular velocity during jumping is about 12–15 rad/s [2628]. …”
Section: Reviewmentioning
confidence: 99%